A case of indirect inguinal bladder hernia treated by laparoscopic hernia repair. Issue 1 (4th June 2020) - Kohga, Atsushi; Okumura, Takuya; Yamashita, Kimihiro; Isogaki, Jun; Suzuki, Kenji; Kawabe, Akihiro
Abstract: Inguinal bladder hernia is a rare clinical condition, and only a small number of reported cases have been treated by laparoscopic surgery. In the present case, the patient was a 78‐year‐old man who presented to our emergency department with a chief complaint of right inguinal bulge and pain. CT imaging revealed an incarcerated right inguinal hernia containing the small intestine and a portion of the urinary bladder. We performed manual reduction of the incarcerated intestine, and he was admitted to the surgical ward for follow‐up. On the 19th day after discharge, recurrence of incarceration developed, and he was readmitted after manual reduction. A laparoscopic transabdominal preperitoneal repair was performed. After careful reduction of the protruding bladder from the hernial orifice, we repaired the right inguinal hernia with a mesh prosthesis. We experienced a rare case of right indirect inguinal bladder hernia that was treated successfully with laparoscopic repair.